Orang Karo diantara orang Batak - Peranginangin, Martin L. (Martin Luther), 1972- (Jakarta : Pustaka Sora Mido, 2004)
History and sociocultural conditions of Karo-Batak people in Indonesia.
Includes bibliographical references (p. 182-184)
Keywords: Karo -- Batak (Indonesian people) -- Social life and customs